The variant T allele of PvuII in ESR1 gene is a prognostic marker in early breast cancer survival - Danny Houtsma (Nature Portfolio, 2021)
Abstract The PvuII (rs2234693) Single Nucleotide Polymorphism (SNP) in the gene coding for the estrogen receptor-1 (ESR1), has been found associated with outcome in tamoxifen treated patients with early hormone-receptor positive breast cancer. However, it remains unclear whether this SNP is a predictive marker for tamoxifen efficacy or a prognostic marker for breast cancer outcome. The aim of this study was to examine the prognostic potential of this SNP in postmenopausal early breast cancer patients treated with adjuvant exemestane. Dutch postmenopausal patients randomised to 5 years of adjuvant exemestane of whom tissue was available (N = 807) were selected from the Tamoxifen Exemestane Adjuvant Multinational (TEAM) trial database. The SNP rs2234693 in the ESR1 gene was genotyped on DNA from formalin-fixed paraffin embedded (FFPE) tumor tissue using Taqman assays and related to the primary endpoint disease-free survival (DFS) and secondary endpoint overall survival (OS). Survival analyses were performed using Cox regression analysis. In total 805 patients were included in the analyses (median follow up of 5.22 years) and genotypes were obtained in 97% of the samples. The variant T allele of PvuII in ESR1 (rs2234693) was associated with a better DFS (hazard ratio (HR) 0.689, 95% confidence interval (CI) 0.480–0.989, P = 0.044) in univariate analysis only, and a better OS in both univariate (HR 0.616, 95%, CI 0.411–0.923, P = 0.019) and multivariate analyses (HR 0.571, 95% CI 0.380–0.856, P = 0.007), consistent with a prognostic rather than a predictive drug response effect. Variation of PvuII in the ESR1 gene is related to OS in postmenopausal, early HR + breast cancer patients treated with exemestane in the TEAM study. Variation in the ESR1 gene may therefore be a prognostic marker of early breast cancer survival, and warrants further research.